Investigation of 500 keV Si ion induced surface structuring of Ni and Ti for enhancement of field emission properties. (15th November 2022) - Ahmad, Shahzeb; Bashir, Shazia; Akram, Mahreen; Amir, Rizwan; Rafique, Muhammad Shahid; Husinsky, Wolfgang; Javed, Mubashir
Abstract : The present paper reports the investigation of surface morphology, elemental composition, phase changes and field emission properties of Si ion irradiated nickel (Ni) and titanium (Ti). The Ni and Ti targets have been irradiated with 500 keV Si ions generated by Pelletron accelerator at various fluences ranging from 6.9 × 10 13 to 77.1 × 10 13 ions/cm 2 . Stopping range of ions in matter analysis revealed higher values of electronic stopping and sputtering yield for Ni as compared with Ti. For both irradiated metals, electronic energy loss dominant over the nuclear stopping. The growth of induced surface structures have been analysed by using field emission scanning electron microscopy (FESEM) analysis. In case of Ni, as the ion fluence increases from 6.9 × 10 13 to 65.8 × 10 13 ions/cm 2, the formation of spherical particulates, agglomers and sputtering is observed. Although in the case of Ti, with the increase of Si ion fluence from 11.6 × 10 13 to 77.1 × 10 13 ions/cm 2, the formation of irregular‐shaped particulates along with crater and sputtered channels is observed. X‐ray diffraction (XRD) analysis shows that no new phase is identified. However, a significant increase in peak intensity is observed with increasing ion fluence. The variation in crystallite size and dislocation line density is also observed as a function of Si ion fluence. Fourier transform infrared spectroscopy analysis shows that no bands are formed after the Si ion irradiation. Field emission properties of ion‐structured Ni and Ti are well correlated with the growth of surface structures observed by SEM and dislocation line density evaluated by XRD analysis.